Fitness costs predict inbreeding aversion irrespective of self-involvement: support for hypotheses derived from evolutionary theory. - Jan Antfolk (Public Library of Science (PLoS), 2012)
It is expected that in humans, the lowered fitness of inbred offspring has produced a sexual aversion between close relatives. Generally, the strength of this aversion depends on the degree of relatedness between two individuals, with closer relatives inciting greater aversion than more distant relatives. Individuals are also expected to oppose acts of inbreeding that do not include the self, as inbreeding between two individuals posits fitness costs not only to the individuals involved in the sexual act, but also to their biological relatives. Thus, the strength of inbreeding aversion should be predicted by the fitness costs an inbred child posits to a given individual, irrespective of this individual's actual involvement in the sexual act. To test this prediction, we obtained information about the family structures of 663 participants, who reported the number of same-sex siblings, opposite-sex siblings, opposite-sex half siblings and opposite-sex cousins. Each participant was presented with three different types of inbreeding scenarios: 1) Participant descriptions, in which participants themselves were described as having sex with an actual opposite-sex relative (sibling, half sibling, or cousin); 2) Related third-party descriptions, in which participants' actual same-sex siblings were described as having sex with their actual opposite-sex relatives; 3) Unrelated third-party descriptions, in which individuals of the same sex as the participants but unrelated to them were described as having sex with opposite-sex relatives. Participants rated each description on the strength of sexual aversion (i.e., disgust-reaction). We found that unrelated third-party descriptions elicited less disgust than related third-party and participant descriptions. Related third-party and participant descriptions elicited similar levels of disgust suggesting that the strength of inbreeding aversion is predicted by inclusive fitness costs. Further, in the related and unrelated conditions alike, the strength of inbreeding aversion was positively associated with the degree of relatedness between those described in the descriptions.